2005
DOI: 10.1007/s10286-005-0283-6
|View full text |Cite
|
Sign up to set email alerts
|

P wave duration and dispersion in multiple sclerosis

Abstract: P wave duration and PWD was found to be statistically different in patients with MS and control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…1). 3 , 7–85 Fourteen of these articles utilized only a computer‐assisted technique for P‐wave evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…1). 3 , 7–85 Fourteen of these articles utilized only a computer‐assisted technique for P‐wave evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…The significance of an increased P wave duration and PDW in our patients is unknown. Kocer et al (2005) investigated P wave duration and dispersion in 31 MS patients and compared with 33 healthy subjects, their study showed that P wave duration and dispersion were prolonged significantly in MS patients compared to control subjects. We cannot find other studies which investigated P wave changes in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors used conventional electrocardiographic (ECG) parameters to make statements about the autonomic dysfunction of the cardiovascular system. Significantly higher maximum P-wave duration and P-wave dispersion (risk factors for atrial fibrillation) were reported in 31 MS patients compared with 33 sex-and age-matched controls [23], and similar findings (along with a non-significant increase in QT interval) were reported from a study in 84 MS patients and 84 age-and sex-matched controls [24]. An Italian study in 31 relapsing-remitting MS (RRMS) patients reported that 16% had an increased QTc interval, which seemed to have a cerebral origin possibly driven by involvement of the insular cortex.…”
Section: Testing For Cad In Msmentioning
confidence: 93%